2017
DOI: 10.1159/000464147
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Dispersal and Immigration in Equatorial Sakis (Pithecia aequatorialis): Factors in the Transition from Pair- to Group-Living

Abstract: Saki monkeys (Pithecia spp.) live in pairs and small groups, sometimes with more than 1 same-sex adult. Previous studies have not been able to distinguish additional, unrelated adults from adult-sized offspring, but both can influence social relationships and mating strategies, albeit in different ways. In this study, we documented the immigration of an adult male equatorial saki (P. aequatorialis) into a group following the departure of the previous resident male. At immigration, the group contained an adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 52 publications
(72 reference statements)
1
14
0
Order By: Relevance
“…Our field studies of sakis have demonstrated that, contrary to their commonly being characterized as “socially monogamous,” there can be substantial variation over time in grouping patterns and in both mating and reproductive behavior, even within the same social group (Porter, Grote, Isbell, Fernandez‐Duque, & Di Fiore, , ). For example, our examination of 12 years of data on group composition and demography for six social groups of sakis indicated that during 45% of group‐months, groups contained two or more adult females and/or two or more adult males (Van Belle, Fernandez‐Duque, & Di Fiore, ).…”
Section: Our Research Program On “Monogamy” In Wild Platyrrhinesmentioning
confidence: 91%
See 1 more Smart Citation
“…Our field studies of sakis have demonstrated that, contrary to their commonly being characterized as “socially monogamous,” there can be substantial variation over time in grouping patterns and in both mating and reproductive behavior, even within the same social group (Porter, Grote, Isbell, Fernandez‐Duque, & Di Fiore, , ). For example, our examination of 12 years of data on group composition and demography for six social groups of sakis indicated that during 45% of group‐months, groups contained two or more adult females and/or two or more adult males (Van Belle, Fernandez‐Duque, & Di Fiore, ).…”
Section: Our Research Program On “Monogamy” In Wild Platyrrhinesmentioning
confidence: 91%
“…However, based on our review of the literature, it seems that throughout the geographic distribution of owl monkeys and titis, virtually all species are pair‐living, making it unlikely that ecological factors are the sole or primary driver of that form of social organization in these two taxa. In contrast, P. aequatorialis , as well as other saki species, deviate from pair‐living, and groups sometimes contain multiple breeding females and mating males (Porter et al, ; Thompson, ; Van Belle, Fernandez‐Duque, & Di Fiore, ). It has not been investigated whether this variation is associated with fluctuations in food availability in space or time.…”
Section: Conclusion and Looking Forwardmentioning
confidence: 99%
“…The floating of individuals without a territory, delayed dispersal and immigration have an important role in the dynamics of the monogamous mating system in pair‐living primates (Jacobs, Frankel, Rice, Kiefer, & Bradley, ; Porter, Grote, Isbell, Fernandez‐Duque, & Di Fiore, ). Unfortunately, there are few studies and data available on the dispersal pattern and dynamics of the social organization in the indri.…”
Section: Discussionmentioning
confidence: 99%
“…For example, groups in socially monogamous primate species can occur as non‐nuclear families if adult pair bonds are not permanent (e.g., Palombit, ). That is, adult individuals in the group might turnover as the result of death, abandonment, or even forcible takeover (e.g., Brockelman, Reichard, Treesucon, & Raemaekers, ; Overdorff & Tecot, ; Palombit, ; Porter, Grote, Isbell, Fernandez‐Duque, & Di Fiore, ). Under such circumstances, a new mate might join a group that includes immature individuals that are the offspring of the previous mate, resulting in non‐nuclear family groups.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, adult turnovers in some pair‐living primates might occasionally result in non‐monogamous mating. For example, Porter et al () described a situation among pair‐living sakis ( Pithecia aequatorialis ) in which a resident adult female and her adult‐aged daughter successfully reproduced after a new adult male immigrated into the group, suggesting these births resulted from both females mating with the new male. Thus, variable social organizations and mating strategies can occur in pair‐living species through changes in adult group memberships.…”
Section: Introductionmentioning
confidence: 99%